Toughening of Epoxy Polysulfide Binary Blend Composite - Muzher T. Mohamed (Diyala Journal of Engineering Sciences, 2018)
In a composite structure, it is anticipated that high toughening can be achieved by taking advantage of mixing rubber with epoxy. The purpose of this paper is to investigate the toughness characteristics of Polymeric Composites containing Polysulfide Rubber (PSR) as a toughener to a brittle base epoxy resin. Through comparing with neat resin specimens (epoxy, epoxy +PSR), the results showed that the addition of PSR into polymeric resin enhance toughness of epoxy. Similarly experiment showed that the maximum value of mixing ration is 6% PSR, which cause a noticeable enhancement in composite strain, but a reduction in tensile strength and modulus of elasticity at fracture.